2018
DOI: 10.1111/odi.12925
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study of oral paracoccidioidomycosis: Analysis of 320 cases and literature review

Abstract: Oral paracoccidioidomycosis is an uncommon lesion observed in oral biopsy samples. The differences in the relative frequency of oral paracoccidioidomycosis are related to geographical variations. Men between 50 and 59 years are more affected. This study provides helpful information for clinicians in the diagnosis of oral paracoccidioidomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
48
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 61 publications
5
48
2
7
Order By: Relevance
“…PCM is a leading cause of death from chronic infectious in Brazil, affecting mainly rural workers with mean age of 47 years . Due to the absence of compulsory notification in our country, the accessibility of data about the oral manifestation of PCM is still limited . Interestingly, the oral manifestation of the chronic PCM does not occur in all patients; some authors reported oral involvement in 50% of cases, rising involvement of this site in agreement with patients’ age .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…PCM is a leading cause of death from chronic infectious in Brazil, affecting mainly rural workers with mean age of 47 years . Due to the absence of compulsory notification in our country, the accessibility of data about the oral manifestation of PCM is still limited . Interestingly, the oral manifestation of the chronic PCM does not occur in all patients; some authors reported oral involvement in 50% of cases, rising involvement of this site in agreement with patients’ age .…”
Section: Discussionmentioning
confidence: 89%
“…7,34 Due to the absence of compulsory notification in our country, the accessibility of data about the oral manifestation of PCM is still limited. 9,35 Interestingly, the oral manifestation of the chronic PCM does not occur in all patients 36 ; some authors reported oral involvement in 50% of cases, rising involvement of this site in agreement with patients' age. 37 Nevertheless, there are a few findings capable of explaining the absence of oral lesions in some chronic PCM patients.…”
Section: Discussionmentioning
confidence: 95%
“…introduction Paracoccidioidomycosis (PCM), also known as South American blastomycosis, is a tropical disease caused by the dimorphic fungus Paracoccidioides brasiliensis, initially described by Adolfo Lutz in 1908 1,2 . Although a rare disorder from a global perspective, the disease is endemic in Latin America and is estimated to infect about 10 million Latin Americans.…”
mentioning
confidence: 99%
“…Although a rare disorder from a global perspective, the disease is endemic in Latin America and is estimated to infect about 10 million Latin Americans. In Brazil, PCM is the main cause of death by systemic mycosis, and the eighth cause among infectious diseases 1,3 , with an estimated incidence of approximately 1 to 3.7 cases per million individuals annually 1 . PMC more commonly affects farm workers and/or people who live in rural areas, particularly males, smokers and/or chronic alcoholics, aged between 30 and 50 years 2,3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation